EXPERIMENTAL STUDIES OF THE NOISE SPECTRA IN THE WORKING AREA OF CIRCULAR WOODWORKING MACHINES - B. CH. MESKHI; I. S. VINOGRADOV (Advanced Engineering Research, 2010)
Increased noise is one of the worst, dangerous and harmful production factors. As for circular machines it is mostly characterized by the degree of impact on the operators. Experimental studies of noise during operation of woodworking machines with circular saw blades of various designs have been carried out.